Corporate Social Responsibility in the Zambian Mining Industry; A Multiple Case Study of the Conceptualisation, Implementation and Monitoring processes. - Mumba, Amos (My University, 2009)
The concept of Corporate Social Responsibility (CSR) has developed differently in different parts of the world since its introduction to mainstream literature in the 1950s. In the same line, definitions vary widely and there is no single acceptable model for its implementation even though contemporary literature on the concept is dominated by perspectives from the industrialised world. In that case, is it possible to generalise these western definitions and approaches found in literature or is it possible to develop context specific approaches and models that take into account local economic, social and environmental conditions? To be able to answer these questions, there is need to first understand the awareness levels of the concept in different parts of the world. Therefore, the purpose of this thesis is to understand how the concept of CSR is defined, implemented and monitored in the Zambian mining industry. Results show that there is a very low awareness level of what the concept really is and none of the studied companies has a clear definition. Conclusions further show that all case companies refer to sustainable development principals as the driving force for their approaches focusing on philanthropic gestures; however the study further reveals that only the community development aspect of sustainable development is visible in these companies’ CSR agendas suggesting a lack of understanding of the total concept of sustainable development all together. Furthermore, the study reveals very weak relationships between businesses and their various stakeholders.
Keywords: fi=Management|; fi=Master's Degree Programme in International Business|